Developing Standard Treatment Workflows—way to universal healthcare in India - Grover, Ashoo; Bhargava, Balram; Srivastava, Saumya; Sharma, Lokesh Kumar; Cherian, Jerin Jose; Tandon, Nikhil; Chandershekhar, Sudha; Ofrin, Roderico H.; Bekedam, Henk; Pandhi, Deepika; Mukherjee, Aparna; Dhaliwal, Rupinder Singh; et al. (Frontiers in Public Health, 2023)
Primary health care caters to nearly 70% of the population in India and provides treatment for about 80-90% of common conditions. To achieve Universal Health Coverage (UHC), the Indian healthcare system is gearing up by initiating several schemes like National Health Protection Scheme, Ayushman Bharat, Nutrition Supplementation Schemes, Inderdhanush Schemes etc. The healthcare delivery system is facing challenges like irrational use of medicines, over and under-diagnosis, high out-of-pocket expenditure, lack of targeted attention to preventive and promotive health services, poor referral mechanisms etc. Healthcare providers are unable to keep pace with the volume of growing new scientific evidence and rising healthcare costs, due to a lack of common standard treatment guidelines, workflows and reference manuals from the Government of India. Indian Council of Medical Research in collaboration with the National Health Authority, Govt. of India and the WHO India country office has developed Standard Treatment Workflows (STW) with the objective to be utilized at various levels of health care starting from primary to tertiary level care. A systematic approach was adopted to formulate the STWs. An advisory committee was constituted for planning and oversight of the process. Speciality experts’ group for each speciality comprised of clinicians working at government and private medical colleges and hospitals. The expert groups prioritized the topics through extensive literature searches and meeting with different stakeholders. Then, the contents of each STW were finalized in the form of single-pager infographics. These STWs were further reviewed by an editorial committee before publication. Presently, 122 STWs pertaining to 21 specialities have been developed. It needs to be ensured that STWs are implemented effectively at all levels and ensure quality health care at an affordable cost as part of UHC.